2012
DOI: 10.1029/2012jd018132
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study of the impact of human activity on long‐term temperature change in China: A perspective from energy consumption

Abstract: [1] Human activity is an important contributor to local temperature change, especially in urban areas. Energy consumption is treated here as an index of the intensity of human induced local thermal forcing. The relationship between energy consumption and temperature change is analyzed in China by Observation Minus Reanalysis (OMR) method. Temperature trends for observation, reanalysis and OMR are estimated from meteorological records and 2 m-temperature from NCEP/NCAR Reanalysis 1 for the period 1979-2007. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 45 publications
(51 reference statements)
0
29
0
Order By: Relevance
“…Artificial heat emission and land cover change near the meteorological stations are mainly the results of city expansion or urbanization. Many studies suggested that urbanization has significantly affected surface air temperature change through modifying land cover, air composition and the anthropogenic heat release (Ren et al 2008, Ren andZhou 2014;Zhou and Ren 2009;Hu et al 2010;Zhang et al 2010;Parker 2010;Stewart 2011;Li and Zhao 2012;Wang et al 2012). Ren (2009), Zhang et al (2011a) and Ren and Zhou (2014) found that the single-site and regional-scale urbanization in mainland China had more significantly increased the minimum temperature trends and significantly narrowed the DTR during the past five decades.…”
Section: Discussionmentioning
confidence: 99%
“…Artificial heat emission and land cover change near the meteorological stations are mainly the results of city expansion or urbanization. Many studies suggested that urbanization has significantly affected surface air temperature change through modifying land cover, air composition and the anthropogenic heat release (Ren et al 2008, Ren andZhou 2014;Zhou and Ren 2009;Hu et al 2010;Zhang et al 2010;Parker 2010;Stewart 2011;Li and Zhao 2012;Wang et al 2012). Ren (2009), Zhang et al (2011a) and Ren and Zhou (2014) found that the single-site and regional-scale urbanization in mainland China had more significantly increased the minimum temperature trends and significantly narrowed the DTR during the past five decades.…”
Section: Discussionmentioning
confidence: 99%
“…Collecting such detailed energy consumption data is a formidable task in many countries and regions. With the top-down inventory approach, the energy consumption data from energy statistics on a province-level scale or a larger spatial scale are downscaled to smaller scales, based on a finer spatial indicator, for example, population density, land use data, gross domestic product (GDP) data, and nighttime light data [14,20,25]. In China, the statistical energy consumption data on the province-level scale can be obtained from the China Energy Statistical Yearbook.…”
Section: Mapping Statistical Energy Consumption Datamentioning
confidence: 99%
“…With rapid economic development, more fossil fuels have been consumed, which produced a great deal of greenhouse gases (GHGs) as well as energy (Barnett and O'Neill, 2010). The released GHGs and heat have induced a strong influence on temperature spatial distribution in recent years (Li and Zhao, 2012), especially in developing countries, where the economic policy relies on extensive growth, which favours results, despite lower resource efficiency and energy waste. Jiang and Hardee (2011) noted that main factors influencing anthropogenic effects on aerosol emission are economic growth, technological change, and population growth, which cannot be easily simulated using numerical models (Zhou et al, 2010).…”
Section: Introductionmentioning
confidence: 99%